Classification of aorta insufficiency and stenosis using neuro-fuzzy system - Barişçi, Necaattin; Topal, Ergün; Hardalaç, Firat; Güler, Inan (Kluwer Academic/Plenum Publishers, 2005)
Cardiac Doppler signals recorded from aorta valve of 60 patients were transferred to a personal computer by using a 16 bit sound card. The fast Fourier transform (FFT) method was applied to the recorded signal from each patient. Since FFT method inherently cannot offer a good spectral resolution at jet blood flows such as cardiac Doppler signals, it sometimes causes wrong interpretation. In order to do a good interpretation and rapid diagnosis, cardiac Doppler blood flow signals were statistically arranged and then classified using neuro-fuzzy system. The NEFCLASS model, which is used to create a fuzzy classification system from data, was used. The classification results show that neuro-fuzzy system offers best results in the case of diagnosis. © 2005 Springer Science+Business Media, Inc.
Keywords: Aorta valve; Cardiac Doppler; Fast Fourier transform (FFT); NEFCLASS (neuro-fuzzy classification)